2010
DOI: 10.4038/sjae.v7i0.1825
|View full text |Cite
|
Sign up to set email alerts
|

Pluriactivity and Socio-economic Success of Rural Households

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
1
0
3
Order By: Relevance
“…In the international field, this assumption has also been noted. Silva & Kodithuwakku (2010) observed that, in a Sri Lankan community, not all rural families benefited socially and economically because they were pluriactive, and only families who practiced nonfarm activities that required more skills had a better socioeconomic response. In this same context, Gautam & Andersen (2016), using household data from Nepal, identified that well-being is related to the degree of economic return of nonfarm activities, and not only to diversification itself.…”
Section: Introductionmentioning
confidence: 99%
“…In the international field, this assumption has also been noted. Silva & Kodithuwakku (2010) observed that, in a Sri Lankan community, not all rural families benefited socially and economically because they were pluriactive, and only families who practiced nonfarm activities that required more skills had a better socioeconomic response. In this same context, Gautam & Andersen (2016), using household data from Nepal, identified that well-being is related to the degree of economic return of nonfarm activities, and not only to diversification itself.…”
Section: Introductionmentioning
confidence: 99%
“…A nivel de los países en desarrollo, la participación en actividades no agrícolas aumenta el empleo, la demanda de insumos, la producción agrícola, la renta familiar y reduce la pobreza (Anang, 2017;Awoniyi & Salman, 2011;Babatunde, 2015;Dary & Kuunibe, 2012;Kaur, Kulkarni, Gaiha, & Pandey, 2010;Mehta, 2002;Silva & Kodithuwakku, 2005;. En países africanos como Ghana y Nigeria, las actividades no agrícolas llegan a ocupar entre el 30% y el 60% de las familias rurales (Awoniyi & Salman, 2011;Dary & Kuunibe, 2012).…”
Section: Introductionunclassified
“…Sin embargo, hay muchos estudios que demuestran que las familias agrícolas asociadas a las actividades no agrícolas, como estilo de vida, son más estables que las familias exclusivamente agrícolas (Bryceso, 2002;Davis, 2006;Fuller, 1990;Paudel, 2002), reduciendo la pobreza y las desigualdades (Kaur et al, 2010;Mehta, 2002;Silva & Kodithuwakku, 2005;Zhu & Luo, 2005). En África, por ejemplo, las actividades no agrícolas contribuyen al acceso a los activos productivos, como los animales y las semillas, los fertilizantes, la mejora de la vivienda y hasta la contratación de mano de obra (Cunguara et al, 2011;Feijó & Agy, 2015).…”
Section: Introductionunclassified
“…Η πολυαπασχόληση μειώνει την έκθεση των παραγωγών στη διακύμανση του γεωργικού εισοδήματος που πηγάζει από τον βιολογικό χαρακτήρα και την εποχικότητα της γεωργικής δραστηριότητας και ελαχιστοποιεί τους κινδύνους που απορρέουν από την εξειδίκευση σε μια δραστηριότητα (Stark and Levhari, 1982;Nikajima, 1986;Hetland, 1986;Ellis, 2000;De Silva and Kodithuwakku, 2005).…”
Section: κριτήρια ταξινόμησης πολυαπασχόλησηςunclassified